'Why can't we help protect children too?' Stigma by association among community workers in child protection and its consequences. (6th March 2019) - Hamilton, Sharynne; Cleland, Deborah; Braithwaite, Valerie
Abstract: Community workers provide critical support services to parents and families with children who may be placed in out-of-home care by child protection authorities. Drawing on in-depth interviews with fifteen community workers, who represent nine agencies assisting families with child protection issues in a small jurisdiction in Australia, we show how the stigma attached to 'bad' parents is passed on to the community workers who are supporting them. The 'stigma by association' directed at community workers by child protection authorities means they are stereotyped negatively, undermined professionally and socially excluded. In spite of such stigmatic treatment, community workers remained committed to their professional role. Although workers were frustrated and disappointed in the treatment they received, there was no open acknowledgment of stigma-induced poor mental health. The results are interpreted within a broader social context where child protection authorities are being constantly reviewed and criticized in Australia. The support that community workers give to each other as frontline defenders of families against a powerful and publicly criticized government authority may allow community workers to construe themselves as heroes rather than villains in this highly adversarial environment. The costs play out at the institutional level, however, because reduced trust limits opportunities for genuine collaboration between government and community organizations.